2022
DOI: 10.3201/eid2802.211963
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilaria immitis Pulmonary Dirofilariasis, Slovakia

Abstract: Dirofilaria immitis is a parasite related to pulmonary dirofilariasis in humans, its accidental hosts. We detected an autochthonous case of D. immitis infection in a woman from Slovakia. The emergence and spread of this parasite in Europe indicates a critical need for proper diagnosis of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Mosquitoes transmit the parasites from dogs to humans [78]. Dirofilariasis is diagnosed most commonly in the east coast and southern parts of the United States, with infrequent cases elsewhere in the world [78][79][80][81][82]. A recent study from the Balkan Peninsula reported that two of 46 cases of dirofilariasis were pulmonary infections [80].…”
Section: Pulmonary Dirofilariasismentioning
confidence: 99%
“…Mosquitoes transmit the parasites from dogs to humans [78]. Dirofilariasis is diagnosed most commonly in the east coast and southern parts of the United States, with infrequent cases elsewhere in the world [78][79][80][81][82]. A recent study from the Balkan Peninsula reported that two of 46 cases of dirofilariasis were pulmonary infections [80].…”
Section: Pulmonary Dirofilariasismentioning
confidence: 99%
“…)), together with fine-needle aspirate (FNA) and histological examination of nodules when present ( 3 , 12 , 17 , 18 ). Serological tests are available as reference laboratory assays and also point-of care (POC) tests ( 3 , 19 21 ). While for D. immitis , one can rely on rapid and straightforward in-clinic test kits together with several serological laboratory tools, no similar tests are available for D. repens ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies on the incidence and/or prevalence of Dirofilaria spp. infection in the same canine population have shown differing results according to the diagnostic method adopted ( 15 , 18 , 19 , 30 ). For this reason, diagnosis of animal dirofilariosis must rely on the integration of results from at least two methods in order to reduce the risk of false positives and negatives, as recommended by the AHS ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…This changing trend is likely related to global warming and subsequent increases in vector density and activity during the year. Canine dirofilariasis is endemic in Mediterranean countries of Europe and has 2 main etiologic agents: Dirofilaria repens , the main agent of subcutaneous infections, and D. immitis , the agent largely responsible for cardiopulmonary infections ( 1 – 3 ). Humans are usually dead-end hosts, and infection is mainly caused by a single immature worm ( 2 ).…”
mentioning
confidence: 99%
“…A clinical manifestation of human dirofilarial infection is pulmonary dirofilariasis, which has been predominantly detected within the Americas, although recent cases have been reported in Europe. In addition, D. repens nematodes cause human subcutaneous dirofilariasis (HSD), which is typical of the Old World ( 1 – 3 ); subcutaneous or ocular infection and infections in male genitalia, female mammary glands, lungs, liver, and mesentery have been described.…”
mentioning
confidence: 99%